Adsorption of some Metal Ions from Aqueous Solution on Iraqi Rice Bran and Its Relation to the Physical Properties of these Metal Ions (Baghdad Science Journal, 2014)
Adsorption studies were carried out to test the ability of the Iraqi rice bran (Amber type) to adsorb some metals divalent cations (Cd2+, Co2+, Cu2+, Fe2+, Ni2+, Pb2+, and Zn2+) as an alternative tool to remove these pollutants from water. The Concentrations of these ions in water were measured using flame and flamless atomic absorption spectrophotometry techniques. The applicability of the adsorption isotherm on Langmuir or Freundlisch equation were tested and found to be dependent on the type of ions. The results showed different adsorptive behavior and different capacities of the adsorption of the ions on the surface of the bran. The correlation between the amounts adsorbed and different cation parameters including (electronegativity, ionic radius, and the second ionization potential) were tested. This study showed the applicability of bran, as a cheap and available waste materials, to remove different cations from solution.